Microbial, chemico-physical and volatile aromatic compounds characterization of Pitina PGI, a peculiar sausage-like product of North East Italy. (May 2020) - Iacumin, Lucilla; Osualdini, Milena; Bovolenta, Stefano; Boscolo, Daria; Chiesa, Luca; Panseri, Sara; Comi, Giuseppe
Abstract: Pitina is a fermented sausage-like produced in the mountainous area of the North-East Italy by artisanal plants without the use of both selected starters and casing (Slow Food Presidium). Originally, Pitina has been a way of preserving meat and it is manifactured by meat from ungulates mixed with pork lard, smoked, dryed and ripened. In this study, microbial ecology, physic-chemical parameters, and volatile aromatic compounds of Pitina SR and LR, which differ by the duration of ripening processes, were investigated. Results showed the good hygienic quality. Staphylococcus xylosus and Lactobacillus sakei were responsible for the ripening. Other Coagulase-negative Catalase-positive Cocci (CNCPC) and LAB species were identified: S. equorum, S. warneri, S. succinus and Carnobacterium divergens, Streptococcus equinus, Kocuria rhizophila . Giberella moniliformis and Penicillium turbatum were the only mould species isolated. Strain characterization demonstrated a high genetic variability. Raw meat, environment and ripening conditions seemed to affect strains distribution, which had an impact on the aromatic profile of the product. Highlights: Pitina is a fermented sausage-like made without casing and covered by maize flour. Staphylococcus xylosus and Lactobacillus sakei were responsible for the ripening. Strain characterization demonstrated a high genetic variability. Raw meat, environment and ripening conditions affected strains distribution. The aromatic profile was influenced by the main species involved in seasoning.